Agency Cost as An Intervening Variable in the Impact of Capital Structure and Company Size on Company Performance - Dewi Maryam; Yesa Cahayaning Ramadhani (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
This research was aimed to examine agency cost as an intervening model between capital structure and company size towards the company's performance. Data was collected through non participatory observation method using criteria on issuing consecutive financial statements within the research period. Having the complete financial data that was consistently needed during the research period. The company was not listed during the research period. In this study, the data analysis was conducted using quantitative data analysis with compared ratios and path analysis. The analysis was used due to its possibility of inter-variable relationships in a linear model. The research hypotheses were the effect of capital structure on the company performance, the company size on the company performance, the capital structure of agency cost, the company size on agency cost, and the agency cost on the company performance. As the results, there were direct impact of capital structure, company size, and agency cost on the company's performance. In contrast, there was an indirect impact of capital structure, the size of the company on the company's performance through agency cost as the intervening variable..